INTERPRETASI LAPISAN BAWAH PERMUKAAN DENGAN TRANSFORMASI PSEUDOGRAVITASI BERDASARKAN DATA GEOMAGNETIK PADA MANIFESTASI MATA AIR PANAS KENDALISODO KABUPATEN SEMARANG - Nanang Didik Susilo; Muhammad Irham Nurwidiyanto; Udi Harmoko (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Kendalisodo’s area has geological structures which formed by volcanic Ungaran there are hot springs manifestations has been do secondary geomagnetic data processing obtained in the measurement in Kendalisodo Semarang District. The study aims to interpret the subsurface conditions around the hot springs area Kendalisodo caused the emergence of the hot springs in the area. A total of 63 data points that have been corrected International Geomagnetic Reference Field (IGRF) and daily variation correction is used to make the contours of the total magnetic field anomalies. Contour anomaly magnetic field is then processed using a upward continuation filter, reduction to the pole filter, pseudogravity transformation filter, horizontal and second vertical gradient derivative filter. The results of data processing in the form of total magnetic field anomalies that indicate closure pair of positive and negative closure indicating the fault zone below the surface. This interpretation is supported by the contour anomalyand pseudogravity contour, horizontal gradient which shows that there is a fairly strong density contrast and vertical gradient analysis of the order of two indicates that the fault is a reverse fault type. The interpretation is reinforced also by modeling results that indicate a fault that appears on the rock Gajahmungkur and kaligetas formations in the area Kendalisodo trending northwest-southeast. This fault zone is a media outlet fluid to the surface that appears as the source of the hot springs